Labor in the Time of Trump - Clawson, Dan; Juravich, Tom; Hammonds, Clare; Weinbaum, Alys Eve, 1967-; Kerrissey, Jasmine, 1977- (Book collections on Project MUSE., 2019)
Labor in the Time of Trump critically analyzes the right-wing attack on workers and unions and offers strategies to build a working-class movement. While President Trump's election in 2016 may have been a wakeup call for labor and the Left, the underlying processes behind this shift to the right have been building for at least forty years. The contributors show that only by analyzing the vulnerabilities in the right-wing strategy can the labor movement develop an effective response. Essays in the volume examine the conservative upsurge, explore key challenges the labor movement faces today, and draw lessons from recent activist successes.